Principal managerial skills and teachers job effectiveness in secondary schools in Calabar Educational Zone, Cross River State, Nigeria. (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
The study examined the relationship between Principals Managerial Skills and Teachers Job Effectiveness in Public Secondary Schools in Calabar Education Zone Cross River State, Nigeria. Two sub-variables were used for the study. These sub-variables were used to state the purpose of the study, Research Questions and Statement of Hypotheses. The design used for this study was correlation design. The population of the study consisted of two thousand nine hundred and thirty-three (2933) teachers. Stratified sampling technique was used for this study. A sample size of five hundred and eighty-six (586) teachers were selected for the study. Instrument titled; Principals managerial skills and Teachers Job Effectiveness questionnaire (PMSTJEQ) was used for data collection. The instrument was validated by two experts in the department of test and measurement who ensured every item used measure what it supposed to measure. Cronbach Alpha reliability estimate of 0.76 to 0.92 was obtained. Pearson product moment correlation statistics was used for data analysis. The result of the findings revealed that there is a significant relationship between Principals innovative skills, Decision making skills, and Teachers Job Effectiveness. It was therefore recommended that School Principals should demonstrate good managerial skills that will create a supportive environment where Teachers feel valued and empowered, ultimately improving teaching effectiveness and enhancing student’s outcomes. Effective decision-making skills are crucial for school principals to ensure that their leadership positively impacts students, teachers and the broader community.
Keywords: Managerial skills; innovative skills; decision making skills and teachers job performance